Penguatan Nilai Moderasi Beragama melalui Ajaran Pendidikan Agama Islam - solihin, Mohamad; Hakim, Lukman (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
Religious moderation is an important foundation for creating harmony in rural communities that often have diverse dynamics. Islamic education in the village has a strategic role in instilling the values ​​of religious moderation, especially in the younger generation and the general public. This study aims to analyze the role of Islamic education teachings in Semampir village in strengthening the values ​​of religious moderation. A phenomenological approach with qualitative research is used with in-depth interview methods, field observations and literature literacy studies. The results of the study indicate that Islamic education teachings can strengthen the values ​​of religious moderation, including: 1) Instilling Tolerance Values ​​2) strengthening noble morals 3) involvement of religious leaders. Meanwhile, the implementation of religious moderation values ​​in this village is carried out through various approaches that involve the active participation of the Semampir village community. Some concrete steps taken include religious studies, interfaith dialogue, and socio-religious activities.